Significant Reduction in Lattice Thermal Conductivity of (PbTe)0.95 - (PbS)0.05 Thermoelectric Materials Through Liquid Silicon Quenching - Ginting, Dianta; Nurlela, Ai; Nanto, Dwi; Mashadi; Sudiro, Toto; Kristiantoro, Tony; Rhye, Jong-Soo (Science and Technology Indonesia, 2025)
Thermoelectric materials are game-changers, that have the ability to transform waste heat into electrical energy, making them a potential renewable energy solution to reduce reliance on fossil fuels. The standard metric for evaluating thermoelectric materials is the dimensionless figure of merit, ZT, which is markedly influenced by lattice thermal conductivity (ĸl ). Higher thermal transport through the lattice lowers the ZT value, reducing the material’s efficiency. Therefore, finding ways to decrease ????l is critical for boosting thermoelectric performance. In our research, we explored an innovative approach by applying a quenching technique using liquid silicon to reduce thermal conductivity (ĸT ) due to lattice vibrations. We compared the lattice conductivity (ĸl ) of materials with and without this liquid silicon quenching process. The results were striking: at 300 K, quenching lowers the lattice thermal conductivity by about 40.1 %, and at 800 K, it is still reduced by roughly 24.7%compared with pristine PbTe. Even more impressive, when compared to non-quenched (PbTe)0.95 − (PbS)0.05 alloys, at 300 K, the silicon-quenched sample attains an additional ĸl reduction of roughly 16.1 %, while at 800 K the extra decrease is about 13.0%. These findings highlight that liquid silicon quenching is a highly effective method for lowering ĸl of PbTe thermoelectric materials. This approach paves the way for developing next-generation thermoelectric materials that are more efficient, particularly for eco-friendly waste heat recovery applications. Our work opens new possibilities for sustainable energy innovation.